2013
DOI: 10.1007/s12012-013-9205-3
|View full text |Cite
|
Sign up to set email alerts
|

Coumaric Acid Induces Mitochondrial Damage and Oxidative-Mediated Cell Death of Human Endothelial Cells

Abstract: Evidence that higher natural antioxidants (NA) intake provides cardiovascular protection is contradictory. The endothelium plays a pivotal role in cardiovascular homeostasis, and for this reason, the molecular events resulting from the interaction of NA with endothelial cells (ECs) are actively investigated. Here, we show that moderately high doses of coumaric acid (CA) induced intracellular reactive oxygen species (ROS) production, mitochondrial membrane depolarization and ECs death. Treatment of ECs with cyc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 33 publications
(22 citation statements)
references
References 30 publications
2
20
0
Order By: Relevance
“…Experimental studies had also found that there was a dose-response curve characterized by stimulation at a low dose and inhibition at a high dose. For example, the researchers used different concentrations of the drug to interfere with endothelial cells and found that cell survival rates decreased as the dose of the drug increased [214,[251][252][253]. This indicates that drugs have the effect of dose-dependent bidirectional regulation.…”
Section: Discussionmentioning
confidence: 99%
“…Experimental studies had also found that there was a dose-response curve characterized by stimulation at a low dose and inhibition at a high dose. For example, the researchers used different concentrations of the drug to interfere with endothelial cells and found that cell survival rates decreased as the dose of the drug increased [214,[251][252][253]. This indicates that drugs have the effect of dose-dependent bidirectional regulation.…”
Section: Discussionmentioning
confidence: 99%
“…A prolonged exposure to RS can induce hypertension, DNA damage, apoptosis (Hodnick et al 1986), mitochondrial dysfunction and endothelial cell death (Posadino et al 2013; Posadino et al 2015). I. paraguariensis contains high concentration of phenolic compounds (Bracesco et al 2011) that can induce to ROS production when they interact with transition metal ions (i.e.…”
Section: A New Approach For Ilex Paraguariensis-mediated Cardioprotecmentioning
confidence: 99%
“…Q10 is an essential co-enzyme, localized at the inner membrane of mitochondria and has several important functions [36,37]. Firstly, Q10 is responsible for electron transfer between complexes I, II and III of the respiratory chain [39][40][41][42]. Secondly, Q10 represents an important proton carrier during this process; and thirdly, it is an important antioxidant for mitochondria under oxidative stress conditions [37,39].…”
Section: Chemical Analysis Of Cells Grown Under Normoxic and Hypoxic mentioning
confidence: 99%
“…Firstly, Q10 is responsible for electron transfer between complexes I, II and III of the respiratory chain [39][40][41][42]. Secondly, Q10 represents an important proton carrier during this process; and thirdly, it is an important antioxidant for mitochondria under oxidative stress conditions [37,39]. For those reasons, we interpret the increased amounts of p-coumaric acid during hypoxia as an indication of Q10 reduction (peak at 2.7 min).…”
Section: Chemical Analysis Of Cells Grown Under Normoxic and Hypoxic mentioning
confidence: 99%